High protein diets and glomerular hyperfiltration in athletes and bodybuilders: Is chronic kidney disease the real finish line? - de Lorenzo, A.; Bomback, A. S.; Mihic, N. (Sports Medicine, 2024)
Several observational and experimental studies in humans have suggested that high protein intake (PI) causes intraglomerular hypertension leading to hyperfiltration. This phenomenon results in progressive loss of renal function with long-term exposure to high-protein diets (HPDs), even in healthy people. The recommended daily allowance for PI is 0.83 g/kg per day, which meets the protein requirement for approximately 98% of the population. A HPD is defined as a protein consumption > 1.5 g/kg per day. Athletes and bodybuilders are encouraged to follow HPDs to optimize muscle protein balance, increase lean body mass, and enhance performance. A series of studies in resistance-trained athletes looking at HPD has been published concluding that there are no harmful effects of HPD on renal health. However, the aim of these studies was to evaluate body composition changes and they were not designed to assess safety or kidney outcomes. Here we review the effects of HPD on kidney health in athletes and healthy individuals with normal kidney function.